WEIGHT-LENGTH AND CONDITION FACTOR RELATIONSHIP OF SPERATA SARWARI (SINGHARI), FROM MANGLA LAKE, PAKISTAN - H. A. Shakir; M. R. Mirza A. M. Khan; M. Abid (Journal of Animal and Plant Sciences, 2008)
Fifty fresh water specimens of Singhari, (Sperata sarwari) ranging in total length from 24.9 - 93.7 cm and body weight from 66 - 4824 g were sampled, to study the parameters of weight-length and condition factor relationship from Mangla Lake Pakistan. Log transformed regression were used to test the growth. The value of growth coefficient (b = 3.57) indicates allometric growth in the studied specimens. Condition factor increases with increasing length or weight. The predictive equation can be used to estimate parameters investigated with a fair amount of accuracy within the size range studies. The growth is considered in terms of increase in Formatted: Right: 0 pt, Don't
Keywords: Singhari; Sperata sarwari; weight-length relationship; condition factor